Photocatalytic properties of ZnO/SnO2 nanocomposite films: role of morphology - S. Zarei; M. Hasheminiasari; S.M. Masoudpanah; J. Javadpour (Journal of Materials Research and Technology, 2022)
ZnO-xSnO2 composite films (x = 0, 25, 50, 75, 100 mol%) were deposited by sol–gel spin coating process. The film's microstructural, optical, and photocatalytic properties were studied by various characterization methods such as X-ray diffractometry, Raman spectroscopy, scanning electron microscopy, diffuse reflectance, and photoluminescence spectroscopy. Pure hexagonal ZnO and tetragonal SnO2 phases were formed without additional impurity intermediate phases. The microstructure of composite films showed the distinct morphology with hexagonal ZnO pyramids nucleated on SnO2 nanoparticles, as revealed by the elemental distribution map. The ZnO-25 mol% SnO2 film photodegraded about 70% of methylene blue (MB) dye under ultraviolet irradiation, which was higher than that of the pristine ZnO (5%) and SnO2 (10%) films due to the effective separation of hole–electron pairs, as confirmed by PL spectra.